2003
DOI: 10.1007/bf02914497
|View full text |Cite
|
Sign up to set email alerts
|

Timing of laparoscopic cholecystectomy in acute cholecystitis

Abstract: Early laparoscopic cholecystectomy is the treatment of choice for acute cholecystitis, but is associated with a high conversion rate independent of the timing of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Our results show that, even in a teaching hospital, conversion rates are relatively higher in elective cases (8.8%-16.5%), but still We chose to use the day of admission as a reference for time measurement instead of the first day of symptoms. Eldar and colleagues used the first day of symptoms as a reference and found higher conversion rates (39%), but no increase in complication rates with delays of more than 48 h, and this finding was supported by others [5,7,18]. Onset of symptoms is a subjective parameter, and therefore in many hospitals it is the day of admission and the initiation of conservative treatment that is the main guide to operative scheduling [2].…”
Section: Discussionmentioning
confidence: 73%
“…Our results show that, even in a teaching hospital, conversion rates are relatively higher in elective cases (8.8%-16.5%), but still We chose to use the day of admission as a reference for time measurement instead of the first day of symptoms. Eldar and colleagues used the first day of symptoms as a reference and found higher conversion rates (39%), but no increase in complication rates with delays of more than 48 h, and this finding was supported by others [5,7,18]. Onset of symptoms is a subjective parameter, and therefore in many hospitals it is the day of admission and the initiation of conservative treatment that is the main guide to operative scheduling [2].…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, the definition of early operation has ranged from 2 days [16], 3 days [17], to 4 days [18] from onset of symptoms. Others suggest that a high conversion rate for emergency laparoscopic cholecystectomy is independent of the timing of surgery [19,20].…”
mentioning
confidence: 99%
“…In our study, 106(21.9% ) patients presented with acute cholecystitis. But in a study by Cheema, 120 out of 132 (90.91%) cases of cholelithiasis were in acute cholecystitis 9 while Ludwig et al 10 and Serratic et al 6 have reported 71.9% and 41.84% cases respectively in acute phase. In our study, the maximum number of patients was operated within 24 hours while a study by Johansson has reported that early laparoscopic cholecystectomy may be carried out within 7 days of onset of symptoms 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Per-operative complications in this study included bleeding in 11(10.3%) cases, CBD injury in 5(4.71%), minor injury to liver in 5(4.71% ) and distorted anatomy of Calot's triangle in 10 (9.43% ) cases respectively. Meanwhile, in Cheema's study, 3 bile duct injuries have been reported among 482 cases 9 . However, early recognition and prompt repair gives good results 18 .…”
Section: Paralytic Ileusmentioning
confidence: 99%